2021
DOI: 10.1111/rode.12834
|View full text |Cite
|
Sign up to set email alerts
|

Government spending and the exchange rate: Exploring this relationship in Mexico using a cointegrated system of equations

Abstract: The main aim of this paper is to empirically test the effect of both public consumption and investment on the exchange rate in the Mexican economy. Recent increasing literature on the topic has pointed out that effects in either direction of disaggregated public expenditure on the exchange rate can be expected. Therefore, we investigate this using a system of cointegrated equations. The simulations’ results suggest that expansions of government consumption leave unchanged the real exchange rate and depreciate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…At the same time, public expenditures are mostly made for goods produced in a certain country, thus leading to a growth in the demand for national goods in relation to imported ones, stimulating competitiveness through the real appreciation of the exchange rate. This is the main output obtained in several empirical works (Di Giorgio et al, 2018;Cruz & Sánchez-Vargas, 2022). The opposite result of increasing competitiveness implies that, through public spending, fiscal policy leads to a decrease in competitiveness (Médici et al, 2021).…”
Section: Introductionmentioning
confidence: 83%
“…At the same time, public expenditures are mostly made for goods produced in a certain country, thus leading to a growth in the demand for national goods in relation to imported ones, stimulating competitiveness through the real appreciation of the exchange rate. This is the main output obtained in several empirical works (Di Giorgio et al, 2018;Cruz & Sánchez-Vargas, 2022). The opposite result of increasing competitiveness implies that, through public spending, fiscal policy leads to a decrease in competitiveness (Médici et al, 2021).…”
Section: Introductionmentioning
confidence: 83%
“…Neoclassical economists posit that government consumption expenditure on goods and services affect both the output and investment. Moritz and Armando (2021) examined the relationship between government spending and exchange rate in Mexico for the period 1990-2018, using the techniques of autoregressive distributed lag (ADL). Their finding showed that a rise in government consumption leads to a marginal depreciation in the nominal exchange rate.…”
Section: Government Final Consumption Expenditure and Exchange Rate R...mentioning
confidence: 99%